Cardiorespiratory and hemogasometric effects of epidural ketamine and its associations with morphine and xylazine in sheep - Ceci Ribeiro Leite; Fabio Otero Ascoli; Juliana de Oliveira; Daniel Andrews de Moura Fernandes; Jeferson Ferreira da Fonseca; Felipe Zandonadi Brandão (Semina: Ciências Agrárias, 2021)
This study aimed to evaluate the cardiorespiratory and hemogasometric effects of epidural ketamine and its associations with morphine and xylazine in ewes submitted to transcervical cervix transposition with a hegar dilator. Ten Santa Inês breed ewes were studied in a cross over model study where three epidural protocols (GK = ketamine 2.0 mg kg-1; GKM = ketamine 2.0 mg kg-1 + morphine 0.1 mg kg-1; GKX = ketamine 2.0 mg kg-1 + xylazine 0.05 mg kg-1) were compared among each other and with a control treatment (GS= saline 1 mL/7.5 kg). The assessed variables were heart rate, respiratory frequency, ear temperature, non-invasive blood pressure and hemogasometric analysis. All parameters were assessed at baseline and then ewes were sedated with an association of acepromazine (0.1 mg kg -1) and diazepam (0.2 mg kg -1). Ten minutes after sedation all parameters were reassessed and afterwards the epidural injections were performed. Hemogasometry was repeated at 15 and 30 minutes after epidural and the other parameters assessed at 05, 15, 30, 45 and 60 minutes after epidural. GKX showed a slight respiratory depression with lower levels of PO2 and a compensatory increase in respiratory frequency. GKM presented the lower temperature mean. All protocols showed few cardiorespiratory effects when compared with control. Epidural with 2.0 mg kg-1 ketamine isolated was considered the best option for short procedures as obstetric manipulations in sheep due to its cardiorespiratory stability when compared with the protocols using associations.